2019
DOI: 10.1177/0271678x19884742
|View full text |Cite
|
Sign up to set email alerts
|

HDAC4 and HDAC5 form a complex with DREAM that epigenetically down-regulates NCX3 gene and its pharmacological inhibition reduces neuronal stroke damage

Abstract: The histone deacetylases (HDACs)-dependent mechanisms regulating gene transcription of the Na+/Ca+ exchanger isoform 3 ( ncx3) after stroke are still unknown. Overexpression or knocking-down of HDAC4/HDAC5 down-regulates or increases, respectively, NCX3 mRNA and protein. Likewise, MC1568 (class IIa HDACs inhibitor), but not MS-275 (class I HDACs inhibitor) increased NCX3 promoter activity, gene and protein expression. Furthermore, HDAC4 and HDAC5 physically interacted with the transcription factor downstream r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 47 publications
(90 reference statements)
0
30
0
Order By: Relevance
“…61,82 After transient MCAO in rats, overexpression or knockdown of HDAC4 and HDAC5, was shown to decrease or increase the expression of the neuroprotective Na þ /Ca 2þ exchanger 3 (NCX3), respectively. 83 RNA silencing of HDAC9 reduced endothelial injury and improved BBB integrity, thereby reduced inflammation, edema, and infarct following transient MCAO in rats. 84 HDAC9 expression was increased in the carotid plaques of stroke patients 85 and a single nucleotide polymorphism (SNP) in the HDAC9 gene has been associated with large artery atherosclerotic stroke in multiple stroke patient studies.…”
Section: Stroke and Histone Acetylationmentioning
confidence: 92%
“…61,82 After transient MCAO in rats, overexpression or knockdown of HDAC4 and HDAC5, was shown to decrease or increase the expression of the neuroprotective Na þ /Ca 2þ exchanger 3 (NCX3), respectively. 83 RNA silencing of HDAC9 reduced endothelial injury and improved BBB integrity, thereby reduced inflammation, edema, and infarct following transient MCAO in rats. 84 HDAC9 expression was increased in the carotid plaques of stroke patients 85 and a single nucleotide polymorphism (SNP) in the HDAC9 gene has been associated with large artery atherosclerotic stroke in multiple stroke patient studies.…”
Section: Stroke and Histone Acetylationmentioning
confidence: 92%
“…HDAC4 and HDAC5 physically interact with the transcription factor downstream regulatory element antagonist modulator (DREAM). A recent study showed that the DREAM/HDAC4/HDAC5 complex epigenetically down-regulates ncx3 gene transcription after stroke, and the pharmacological inhibition of class IIa HDACs reduces stroke-induced neurodetrimental effects [ 40 ].…”
Section: Histone Deacetylasesmentioning
confidence: 99%
“…HDAC inhibitors (iHDACs), which were effective in protecting the brain from ischemic damage, belonged to two chemical groups: (a) small carboxylates: valproic acid (VPA), sodium butyrate (SB), and sodium 4-phenylbutyrate (4-PBA); (b) Hydroxamate-containing compounds: suberoylanilide hydroxamic acid (SAHA) and trichostatin A (TSA) and others [ 55 ]. In cellular and animal models of ischemia, iHDACs have been shown to protect the brain from excitotoxicity, oxidative stress, endoplasmic reticulum stress, apoptosis, inflammation, and BBB damage [ 40 , 56 , 57 ]. They also promote angiogenesis, neurogenesis, and stem cell migration to damaged areas, which leads to functional recovery after brain ischemia [ 58 , 59 ].…”
Section: Biological Activity Of Hdac Inhibitorsmentioning
confidence: 99%
“…Ischemia alters the expression of multiple HDAC proteins, and these have become popular targets for preclinical neuroprotection studies in stroke [ 63 ]. Recent studies have demonstrated protective effects of HDAC inhibition by anti-inflammation and inhibition of proapoptotic factors in acute treatment of focal cerebral ischemia model of rats (1–6 h after stroke) with various compounds including valproic acid, trichostatin A and sodium butyrate [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ].…”
Section: Epigenetics In Adult Neurogenesis After Strokementioning
confidence: 99%